TEACHING READING COMPREHENSION THROUGH GUIDED NOTE TAKING STRATEGY - Nurul Afiyattena (English Didactic, 2020)
The aim of this study was to examine the effect of Guide note taking strategy on students’ reading comprehension and to identify students’ perception of Guide Note taking strategy. The first grade of one of the Islamic senior high schools in Pandeglang was the participant, there were 31 students tested and surveyed. Pre-experimental (one-group pretest-posttest design) was used to gain students data. The research findings indicated that students’ reading comprehension improve greatly. It showed from the finding results that the value of t(count) was (= 3,77) from significant standard of (α) 5% and 1% of t table was 2,04 and 2,75 then the data analysis showed that t(table) = (2,04) was lower than t(count)= (3,77.) It was marginally estimated that the alternative hypothesis was accepted and Guide Note Taking strategy had positive effect on students’ reading comprehension. Moreover, the survey result showed that students’ perceptions of Guide Note taking was received as well, and the students overwhelmingly supported the use of Guide Note taking strategy, it can be shown from many positive statements gained high percentage. This paper also confirmed that most of the students reading comprehension level included to the literal reading comprehension.